2019
DOI: 10.1111/pbi.13084
|View full text |Cite
|
Sign up to set email alerts
|

Harnessed viruses in the age of metagenomics and synthetic biology: an update on infectious clone assembly and biotechnologies of plant viruses

Abstract: Summary Recent metagenomic studies have provided an unprecedented wealth of data, which are revolutionizing our understanding of virus diversity. A redrawn landscape highlights viruses as active players in the phytobiome, and surveys have uncovered their positive roles in environmental stress tolerance of plants. Viral infectious clones are key tools for functional characterization of known and newly identified viruses. Knowledge of viruses and their components has been instrumental for the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 240 publications
(326 reference statements)
1
68
0
1
Order By: Relevance
“…In contrast to most other biologically-active clones of BNYVV that provide infection through transient genome transcription consequent to Agrobacterium infiltration (i.e., “agro-infection”; [ 44 , 45 , 46 ]), we chose to employ in vitro production of capped RNA transcriptions as the means to produce inoculum for the infection in recipient cells in a manner more consistent with that found in nature. Along with previous reports of others who used NGS data in the construction of clones from which infectious RNA was produced either through in vitro transcription or via agro-infection [ 47 ], our study validates this approach in constructing clones for the study of BNYVV.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to most other biologically-active clones of BNYVV that provide infection through transient genome transcription consequent to Agrobacterium infiltration (i.e., “agro-infection”; [ 44 , 45 , 46 ]), we chose to employ in vitro production of capped RNA transcriptions as the means to produce inoculum for the infection in recipient cells in a manner more consistent with that found in nature. Along with previous reports of others who used NGS data in the construction of clones from which infectious RNA was produced either through in vitro transcription or via agro-infection [ 47 ], our study validates this approach in constructing clones for the study of BNYVV.…”
Section: Discussionsupporting
confidence: 82%
“…Most recently, it has been demonstrated that plant viruses or their derivatives can be used to deliver CRISPR-Cas reagents consisting of single guide RNAs (gRNAs), DNA repair templates, and site-specific nucleases such as Cas9 (Ali et al, 2015;Ali, Eid, Ali, & Mahfouz, 2018;Butler, Baltes, Voytas, & Douches, 2016;Cody, Scholthof, & Mirkov, 2017;Dahan-Meir et al, 2018;Gao et al, 2019;Gil-Humanes et al, 2017;Jiang et al, 2019;Mahas, Ali, Tashkandi, & Mahfouz, 2019;Wang et al, 2017). These capabilities show that plant viruses can be useful biotechnological tools for gene function studies in plants, and they can have practical applications as well (Pasin et al, 2019;Zaidi & Mansoor, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Plant viruses provide surprisingly versatile technology platforms enabling the expression of a wide array of coding and non‐coding sequences in plants (Pasin, Menzel, & Daros, ). Viruses engineered to carry heterologous open reading frames (ORFs) can express the encoded proteins (VOX).…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys underscore the great abundance and diversity of plant viruses that pose major challenges to host defense pathways and, thus, to plant health and food security ( Pasin et al, 2019 ). Multiple layers of defense and complex networks of receptors, small molecules, and transcriptional regulators provide robust plant immunity and tolerance to pathogens ( Nakahara and Masuta, 2014 ; Tsuda and Somssich, 2015 ; Jeon et al, 2017 ; Nobori et al, 2018 ; Paudel and Sanfaçon, 2018 ; Murphy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%